2009
DOI: 10.1186/1758-2652-2-6
|View full text |Cite
|
Sign up to set email alerts
|

From HIV diagnosis to treatment: evaluation of a referral system to promote and monitor access to antiretroviral therapy in rural Tanzania

Abstract: The referral system reduced delays in seeking care, and enabled the monitoring of access to HIV treatment among diagnosed persons. Similar systems to monitor referral uptake and linkages between HIV services could be readily implemented in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…For residents in Kisesa, ART was initially only available via a referral from the local VCT clinics to the zonal referral hospital in Mwanza City, approximately 20 km away. Several qualitative studies identified the long journey time, waiting times at the clinic and a lack of familiarity with the city and intimidation at the very large health facility as barriers to attending the ART clinic at the hospital (Nsigaye et al. 2009; Roura et al.…”
Section: Discussionmentioning
confidence: 99%
“…For residents in Kisesa, ART was initially only available via a referral from the local VCT clinics to the zonal referral hospital in Mwanza City, approximately 20 km away. Several qualitative studies identified the long journey time, waiting times at the clinic and a lack of familiarity with the city and intimidation at the very large health facility as barriers to attending the ART clinic at the hospital (Nsigaye et al. 2009; Roura et al.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was developed based on published evidence indicating that psychosocial factors are common barriers of linkage to HIV care in SSA 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, and that counselling can reduce the effects of these barriers 17, 24, 25, 26, 27, 28 and may increase linkage 6, 7, 9.…”
Section: Methodsmentioning
confidence: 99%
“…Those who were positive in 2006–2007 were referred directly to the hospital for HIV care and treatment. Bus fares and a community volunteer were provided to escort persons to the hospital if they wished (Nsigaye et al. 2009).…”
Section: Methodsmentioning
confidence: 99%
“…VCT is also the main entry point for HIV treatment and care services (De Cock et al. 2003; Nsigaye et al. 2009).…”
Section: Introductionmentioning
confidence: 99%